The value of resilience as a concept for practice in residential settings - Brigid Daniel (Scottish Journal of Residential Child Care)
Resilience is a concept that is increasingly gaining currency as a basis for practice with children and young people. The concept, however, is not easy to define and the term is often used loosely or uncritically so that the implications for practice are unclear. This paper will give a brief overview of the concept, describe some of the pitfalls of its uncritical use and set out a framework for practice. Resilience will be described both as a concept that can help assess a child’s potential strengths and as a framework for practice. Much of what is indicated for practice is what practitioners and carers already do; however, the concept of resilience helps to set a conceptual framework around that work and provides a theoretical basis for what, in many cases, seems like common sense (Daniel, Wassell and Gilligan, 1999).